Long‐term outcomes of children after prenatal exposure to maternal cancer and its treatment - Evangeline A. Huis in ’t Veld; Indra A. Van Assche; Frederic Amant (Acta Obstetricia et Gynecologica Scandinavica)
Abstract The incidence of antenatal cancer is increasing, prompting a medical‐ethical evaluation. The International Network on Cancer, Infertility, and Pregnancy (INCIP) was established to study cancer treatment safety during pregnancy and its impact on maternal and child health. Pivotal research has led to a paradigm shift in clinical management, demonstrating the feasibility and safety of most antenatal oncological treatments. Short‐term outcomes reveal normal growth and cardiac function in the exposed offspring, but caution is advised against first‐trimester chemotherapy. Psychological impact studies highlight the elevated levels of distress in pregnant cancer patients, underscoring the need for personalized information and ongoing psychological support. Long‐term follow‐up studies address gaps in postnatal impacts, while research into specific chemotherapeutic agents continues. Despite generally reassuring outcomes, continued monitoring is crucial, especially in families, such as those where the child was born premature after cancer (treatment) during pregnancy or where mothers are frequently absent due to continued illness or have died from. The ongoing INCIP child follow‐up initiative aims to further elucidate knowledge gaps, emphasizing the importance of large‐scale studies and personalized patient care.